Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Of course! Let's break down the expression step-by-step and solve it:
We need to calculate the sum of the following numbers:
[tex]\[ -10 + (-2) + (+3) + (-15) \][/tex]
Here's how we can solve it step-by-step:
1. First, manage the addition of the first two numbers:
[tex]\[ -10 + (-2) = -10 - 2 = -12 \][/tex]
2. Next, add the third number to the result:
[tex]\[ -12 + (+3) = -12 + 3 = -9 \][/tex]
3. Finally, add the last number to the result:
[tex]\[ -9 + (-15) = -9 - 15 = -24 \][/tex]
So, when we combine all the steps together, we get:
[tex]\[ -10 + (-2) + (+3) + (-15) = -24 \][/tex]
Therefore, the result is [tex]\( -24 \)[/tex].
We need to calculate the sum of the following numbers:
[tex]\[ -10 + (-2) + (+3) + (-15) \][/tex]
Here's how we can solve it step-by-step:
1. First, manage the addition of the first two numbers:
[tex]\[ -10 + (-2) = -10 - 2 = -12 \][/tex]
2. Next, add the third number to the result:
[tex]\[ -12 + (+3) = -12 + 3 = -9 \][/tex]
3. Finally, add the last number to the result:
[tex]\[ -9 + (-15) = -9 - 15 = -24 \][/tex]
So, when we combine all the steps together, we get:
[tex]\[ -10 + (-2) + (+3) + (-15) = -24 \][/tex]
Therefore, the result is [tex]\( -24 \)[/tex].
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.